Swarm intelligence. Volume 3, - Tan, Ying, 1964- (IET control, robotics and sensors series, 2018)
The book focuses on presenting some typical and latest real-world applications in swarm intelligence and related evolutionary algorithms. In particular, in the book, we intend to present the latest and inspiring applications of swarm intelligence and some evolutionary algorithms, including the applications of well-known swarm intelligence algorithms and some other general applications to show the effectiveness and validation of swarm intelligence and encourage more and more researchers and practitioners to use them in their ongoing projects as well as attract more and more newcomers to this prospect area.